The Control Environment; A Panacea for Effective Internal Control System in Nigeria's Public Service Entities (Global Journal of Management and Business Research, 2024)
The study has examined the control environment one of the five components of the COSO internal control integrated framework; which is widely accepted as a model for evaluation of effectiveness of internal control by organizations. Among the five components, the control environment, the focus of this study is widely accepted as the foundation of an organizations entire internal control system. It is generally observed that the internal control system in the Nigerian public entities is very weak, the result is control failures which have given rise to fraud, embezzlement and other corrupt practices which run into billions of naira. The study sought to achieve the following objectives: firstly, identification of factors responsible for weak internal control in public service entities and secondly assessment of the role of the control environment as a panacea to the very weak internal control system in the public service entities in Nigeria. The study is conducted based on desktop and library; both published and unpublished materials were consulted. The study revealed that the managerial style, absence of integrity and ethical values, lack of commitment to competence, organization structure and accountability greatly impact the internal control system in public service entities. The study recommends the adoption of the principles embedded in the control environment for application in the public service entities.
Keywords: control environment; internal control; Panacea; public service entities